The Drying of Foods and its Effect on the Physical-Chemical, Sensorial and Nutritional Properties - Guiné, Raquel (2018)
Drying of foods is an ancient practice that has been adopted to preserve foods beyond their natural shelf life. The process started with the exposure of foods to the sun, to extract from them a great proportion of the water, thus contributing for their conservation. The traditional solar dying with direct exposure to the sun had many disadvantages and presently more modern methods are used, such as hot air drying, spray drying, lyophilization, infrared, microwave or radiofrequency drying, osmotic dehydration or many combined processes.Many foods can be preserved through drying, but their organoleptic and nutritional properties are greatly altered as compared to the fresh counterparts. The objective of this paper is to describe the contents of a plenary speech presentation about the advances in drying methods and the effects of drying on the attributes of the dried foods. For that a search in the scientific literature was conducted and the selection of the information was based on the topics aimed at discussing.